KOORDINASI ANTARA LEMBAGA PENELITIAN DAN PENGEMBANGAN DAERAH DENGAN DEWAN RISET DAERAH GUNA MENDUKUNG PEMBANGUNAN ILMU PENGETAHUAN DAN TEKNOLOGI DI DAERAH : TINJAUAN KONSEP RECIPROCAL COORDINATION - Anugerah Yuka Asmara; Andjar Prasetyo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
The institution for regional research and development and the regional research council are the institutions of science and technology at regional level. In practice, there is an ambiguity of duty and function between both of them. This fact is a factor that causes the weakness of Litbangda and DRD performance in promoting a regional government function. This research to describe the coordination pattern between both of S&T institutions in supporting the development of science and technology at regional level. This research uses a descriptive-qualitative approach. The source of data are the scientific journals, scientific article, books, and the other supporting documents. The data analysis technique uses the interactive data analysis that comprises four stages, 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion withdrawal. The research result shows that the litbangda duty is to conduct several research and development activities in regard to issues of S&T at regional level. While, its function is as a stimulator, motivator, and facilitator for the S&T development clime at regional level. Beside it, the DRD duty is to map out the needs of S&T and to evaluate the S&T policy at regional level. While, its function is as an adviser for a local leader in decision making at regional government level. The bridging strategy of the role of them is through creation a reciprocal coordination pattern. This coordination can promote litbangda and DRD to carry out their duties concurrently. In addition, a local leadership is highly required in promoting the coordination between both of institutions.